ORGANIZING INDEPENDENT LEARNING OF TECHNICAL UNIVERSITY STUDENTS IN THE PROCESS OF TEACHING ENGLISH - Elvina Bakhtiyarovna Yagyaeva (International Journal of Literature and Language Studies, 2026)
This article kind of looks into the theoretical and methodological ground rules behind organizing independent learning for students of technical colleges during English language teaching. It considers how scholarly ideas usually approach autonomous learning, then pinpoints the specific difficulties engineering students meet when they try to master a foreign language outside the classroom, not just in classes. After that, it suggests a more structured framework aimed at boosting self-directed educational activity, like making it easier to keep going on their own and improve learning habits.